Study of Indoor Air Quality in School Buildings in the Argolida Sector of the Peloponnese Region in Greece and Potential Health Risks - Bikaki, Maria Anna; Dounias, Georgios; Cavoura, Olga; Farantos, Georgios; Damikouka, Ioanna; Evrenoglou, Lefkothea (European Scientific Journal, ESJ, 2025)
Aims and Scope: Indoor air quality (IAQ) in schools is crucial, as students spend significant time in school environments in addition to their homes. Epidemiological researches have shown that indoor pollutants are linked to various health and respiratory issues. This paper focuses on investigating the indoor air quality (IAQ) in school buildings in the Argolida sector of the Peloponnese Region in Greece. Methods: The study was conducted in fourteen (14) classrooms across seven (7) school buildings in the Argolida Sector of the Peloponnese Region from March 2022 to May 2023. Physical parameters such as temperature (T) and relative humidity (RH), as well as air pollutants including Carbon monoxide (CO), Carbon dioxide (CO2), Nitrogen dioxide (NO2), Volatile Organic Compounds (VOCs), and Particulate Matter (PM10, PM2.5) were monitored using the series 500 Portable Air Quality Monitor AeroQual. Measurements were taken for one teaching hour per day in each classroom. Due to governmental measures to protect public health from the spread of COVID-19, some windows and doors in the classrooms were opened during sampling. Findings: The mean temperature and relative humidity inside the classrooms were 22.12 oC and 50.87%, respectively. The overall mean concentrations of air pollutants recorded inside the schools were 691.35 ppm CO2, 0.001 ppm NO2, 9.97 ppm VOCs, 15.7μg/m3 PM10, and 11.4μg/m3 PM2.5. No indoor CO concentration (0 ppm) was detected in any of the classrooms. This study indicated the following: a) the indoor CO2 concentration levels in the schools (100%) were below 1000 ppm, b) in five out of the fourteen classrooms (35.7%) within the school buildings, CO2 concentration levels exceeded 700 ppm, and c) the indoor VOCs levels in the schools (100%) were above 0.8 ppm. Eight classrooms (57.1%) in Argolida’s school buildings had no comfort conditions due to high relative humidity (RH > 50%). Statistically significant differences were found for temperature (p= 0.001), CO2 (p < 0.001), NO2 (p=0.006), and VOCs (p=0.001) between indoor and ambient air. Conclusion: The air quality in school buildings in the Argolida sector was affected by the number of students in a classroom, the ventilation rate, and the school’s equipment. The proximity of schools to central roads and construction activities also affected the concentration of indoor air pollutants. Indoor air pollution (IAP) can pose potential health risks. Developing monitoring systems for measuring indoor pollutants in schools, as well as strategies for controlling and improving IAQ, is essential for public health.